Food environment trajectories: a sequence analysis from the CARTaGENE cohort - Habila Adamou; Éric Robitaille; Marie-Claude Paquette; Alexandre Lebel (Cambridge University Press, 2024)
Abstract Objective: The purpose of this study was to create a typology of longitudinal exposure to food environment based on socio-economic context. Design: Food environment trajectories were modelled using a sequence analysis method, followed by a logistic regression to describe those trajectories. Setting: The study took place in Quebec, Canada, using food environment data from 2009, 2011 and 2018 merged with participants' demographic and socio-economic characteristics. Participant: At recruitment, 38 627 participants between the ages of 40 and 69 years from six urban areas in Quebec were included in the CARTaGENE cohort study. The cohort was representative of the Quebec urban population within this age range. Results: Our study revealed five trajectories of food access over time: (1) limited access to food stores throughout the study period, (2) limited access improving, (3) good access diminishing, (4) good access throughout the period and (5) low access throughout the period. Logistic regression analysis showed that participants who were unable to work (OR = 1·42, CI = 1·08-1·86), lived in households with five or more persons (OR = 1·69, CI = 1·17-2·42) and those living in low-income households (OR = 1·32, CI = 1·03-1·71) had higher odds of experiencing a disadvantaged food environment trajectory. Additionally, the level of education and age of participants were associated with the odds of experiencing a disadvantaged food environment trajectory. Conclusions: The study demonstrates that people facing socio-economic disadvantage are more likely to experience a disadvantaged food environment trajectory over time.